Taxonomic and nomenclatural notes on the genus Agrilus Curtis (Coleoptera: Buprestidae: Agrilini) - Jendek, Eduard (Zootaxa, 2005)
The following taxonomic or nomenclatural changes are proposed: Agrilus acastus Kerremans, 1913 (= ohbayashii Tôyama, 1987 syn. nov.); A. adonis Deyrolle, 1864 (= falsulus Obenberger, 1924 syn. nov.); A. albopunctatus Deyrolle, 1864 (= nepos Kerremans, 1900 syn. nov.); A. angustulus (Illiger, 1803) (= laeticeps Semenov, 1890 syn. nov.); A. basilewskyanus Descarpentries & Villiers, 1963 correct original spelling; A. birmanicus Kerremans, 1892 (= legitimus Obenberger, 1936 syn. nov.); A. cairnensis Obenberger, 1959 correct original spelling (= cairnsensis Curletti, 2001 unjustified emendation syn. nov.); A. chekiangensis Gebhardt, 1929 (= semivittatus Tôyama, 1985 syn. nov.); A. confutus Obenberger, 1936 (= conjectus Obenberger, 1936 syn. nov.); A. convergens Fisher, 1930 (= japanensis Obenberger, 1935 syn. nov.); A. croaticus Abeille de Perrin, 1897 (= serbicus Obenberger, 1927 syn. nov.); A. cyanipennis Gory & Laporte, 1837 (= ornativentris Saunders, 1866 syn. nov.; = agilis Kerremans, 1894 syn. nov.; = amabilicolor Obenberger, 1936b syn. nov.); A. decoloratus decoloratus Kerremans, 1892 (= afghanistanicus Alexeev in Alexeev, Volkovitsh & Kabakov, 1992 syn. nov.); A. dignus Kerremans, 1912 (= csikii Gebhardt, 1925 syn. nov.; = kayan Fisher, 1930 syn. nov.); A. discicollis Deyrolle, 1864 (= punctiventris Kerremans, 1900 syn. nov.); A. ecarinatus Marseul, 1866 (= gracilicornis Ganglbauer, 1890 syn. nov.); A. erythrostictus Bourgoin, 1922 (= barmensis Obenberger, 1936 syn. nov.); A. fleischeri Obenberger, 1925 (= kurosawai Obenberger, 1940 syn. nov.; = tscherepanovi Stepanov, 1954 syn. nov.); A. lineariformis new replacement name (= lineatus Kerremans, 1899 syn. nov.); A. maculiventris Deyrolle, 1864 (= opulentus Kerremans, 1900b syn. nov., = woodlarkianus Kerremans, 1900c syn. nov., = viridissimus Cobos, 1964 syn. nov.); A. marginicollis Saunders, 1873 (= beppuensis Obenberger, 1936 syn. nov.); A. moerens Saunders, 1873 (= araxicola Abeille de Perrin, 1897 syn. nov.); A. monogrammus Thomson, 1879 (= kabakovi Alexeev in Alexeev,Volkovitsh & Kabakov, 1992 syn. nov.); A. ocularis Deyrolle, 1864 (= bidentellus Obenberger, 1924 syn. nov.); A. paganettii Obenberger, 1913 (= pisanus Curletti, 1980 syn. nov.); A. perniciosus Deyrolle, 1864 (= perniciosus Obenberger unavailable name, = subperniciosus Obenberger, 1936 unavailable name); A. perviridis Kerremans, 1894 (= singaporensis Obenberger, 1924 syn. nov.); A. quadrisignatus Marseul, 1866 (= mongoliae Obenberger, 1922; = lama Obenberger, 1935 syn. nov.); A. sospes Lewis, 1893 (= kinoshitae Obenberger, 1936 syn. nov.; = quadristictulus Oben-